STRATEGY FOR INTRODUCING BASIC CALITUNG TO CHILDREN AGED 5-6 YEARS AT ALWAHIDA PAUD, MATARAM CITY IN THE 2023/2024 ACADEMIC YEAR - Wahyuni, Wahyuni (JOETAL: Journal of Education, Teaching and Learning, 2025)
This research is motivated by the pros and cons of basic reading, writing, and arithmetic learning at the Early Childhood Education (PAUD) level, as well as the implementation of basic reading, writing, and arithmetic in Alwahida PAUD, which is predominantly implemented using fun strategies. The purpose of this study was to determine the strategies and obstacles in introducing basic reading, writing, and arithmetic in grade B of Alwahida PAUD Mataram in the 2023/2024 academic year. This research is a descriptive qualitative study, with data sources from grade B teachers and the principal. Data collection techniques were observation, interviews, and documentation. Data analysis techniques included data reduction, data presentation, and data verification. Data validity was achieved through increased diligence and data triangulation. The results of this study are: (1) The introduction of basic reading, writing, and arithmetic to children aged 5-6 years at Alwahida PAUD was implemented in grade B using five strategies: letter cards, quizzes, magazine assignments, writing in a boxed book, and attendance activities. (2) The implementation of basic reading, writing, and arithmetic at Alwahida Preschool (PAUD) encountered two obstacles: children's poor mood upon arrival at school, resulting in a lack of enthusiasm for participating in activities, and factors such as age and ability to absorb the material.